2013
DOI: 10.1002/pssa.201329146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quenching rate on the average grain size and martensitic transformation temperature in rapidly solidified polycrystalline Ni50Mn37Sn13 alloy ribbons

Abstract: The present investigation was undertaken to investigate the effect of quenching rate on the microstructure of Ni 50 Mn 50 À x Sn x ribbon alloys and its influence on the martensitic starting phase-transition temperature M S . The study was performed on melt-spun ribbons of a ferromagnetic shape memory alloy (FSMA) of composition Ni 50 Mn 37 Sn 13 produced by varying the speed of the rotating copper wheel between 15 and 50 m s À1 . The resulting samples have a chemical composition close to the nominal one and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
(66 reference statements)
1
16
1
Order By: Relevance
“…Nevertheless, a thermodynamic approach is not enough to explain the sample behavior. From the microstructural point of view, the main conclusion is that small grains have a stabilizing effect in the austenitic phase increasing thermal hysteresis, probably because they limit the volume of the individual martensite variants [15,24]. Consequently, in our work it was found that thermal hysteresis is lower/higher in samples with higher/lower grain size and thickness (R3 and R4 / R1 and R2).…”
Section: Resultsmentioning
confidence: 47%
See 2 more Smart Citations
“…Nevertheless, a thermodynamic approach is not enough to explain the sample behavior. From the microstructural point of view, the main conclusion is that small grains have a stabilizing effect in the austenitic phase increasing thermal hysteresis, probably because they limit the volume of the individual martensite variants [15,24]. Consequently, in our work it was found that thermal hysteresis is lower/higher in samples with higher/lower grain size and thickness (R3 and R4 / R1 and R2).…”
Section: Resultsmentioning
confidence: 47%
“…For practical purposes, a good estimation of both terms can be made in accordance with reference [24]: and:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the bulk, the ribbon samples of these NiMn-based FSMAs have also attracted increasing attention because rapid quenching by melt spinning is an effective method to synthesize highly textured polycrystalline samples, which can reduce or even avoid the prolonged annealing process [23][24][25][26][27][28][29][30][31][32][33][34]. Ribbons are appropriate MCE materials in practical applications because they can improve the technical characteristics of a refrigeration unit by optimizing the heat transfer between the working body and heat exchange [31].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Gd 5 (Si x Ge 1-x ) 4 [1,16], La(Si,Fe,X) 13 (X= Co, Mn) [17,18], MnFe(P,X) with X = As, Ge, Si [6,19], non-stoichiometric NiMn-X-based Heusler-type (X= Ga, Sn, In, Sb) [20][21][22][23][24][25][26] or Mn(Co,Ni)Ge-based alloys [27][28][29][30][31][32][33][34][35][36][37]. It is worth noting that MnCoGe-based alloys have one of the largest contributions of S st to S T , giving rise to one of the highest reported GMCE in terms of the maximum value of S T [14].…”
Section: M( O H) Through the Maxwell Relation For Materials Undergoimentioning
confidence: 99%